Psychographic Segmentation of Individuals Interested in Celtic Christianity: Developing a Celtic Christianity Type Scale - Hall, Gillian L. (Rural theology, 2023)
This study uses Jungian psychological type theory as developed by various type measures as a lens through which to explore those aspects of Celtic Christianity that attract individuals to this type of spirituality. Data were provided by 509 individuals who completed an on-line questionnaire that included Celtic Christianity items conceptually linked with the four psychological type functions, sensing, intuition, thinking and feeling. Analysis of the results led to the creation of Celtic Christianity Type Scales which identified those aspects of Celtic Christianity that might reflect the appeal of sensing, intuition, thinking and feeling to this form of spirituality. Each scale achieved an acceptable level of internal consistency reliability.